2019
DOI: 10.12911/22998993/110841
|View full text |Cite
|
Sign up to set email alerts
|

Length-Weight Relationship and Condition Factor of Mudskipper Boleophthalmus pectinirostris from Maro Estuary, Merauke Regency, Papua

Abstract: This study aimed at analyzing the length-weight relationship and the condition factors of Boleophthalmus pectinirostris originating from the Maro estuary, Merauke Regency, Papua Province, Indonesia. This study was conducted for three months, starting from July to September 2018. This study used a purposive sampling method. The sampling of B. pectinirostris was carried out at two stations by using traps and capturing manually. 80 fish of B. pectinirostris were caught during the study. The length size of males 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Thus, it can be concluded that the increase in length has a significant effect on the increase in weight. Similarly, Sunarni et al (2019) also found that female B. pectinirostris has positive allometric growth patterns with determination coefficient value of (R 2 = 0.9796-0.9784), where there was a strong correlation between the length and the weight of B. pectinirostris. Positive allometric growth of mudskipper was also found in male P. barbarous (Indarjo et al 2020), P. argentilineatus and P. spilotus (Khaironizam and Norma-Rashid 2002), and P. crysospilos (Abdullah and Zain 2019).…”
Section: Length-weight Relationship Of Mudskippermentioning
confidence: 63%
See 2 more Smart Citations
“…Thus, it can be concluded that the increase in length has a significant effect on the increase in weight. Similarly, Sunarni et al (2019) also found that female B. pectinirostris has positive allometric growth patterns with determination coefficient value of (R 2 = 0.9796-0.9784), where there was a strong correlation between the length and the weight of B. pectinirostris. Positive allometric growth of mudskipper was also found in male P. barbarous (Indarjo et al 2020), P. argentilineatus and P. spilotus (Khaironizam and Norma-Rashid 2002), and P. crysospilos (Abdullah and Zain 2019).…”
Section: Length-weight Relationship Of Mudskippermentioning
confidence: 63%
“…The negative allometric growth of P. papilio is shown that the body length grows faster than the body weight, resulting in more flattened mudskipper (Moslen and Daka 2017). In addition, Sunarni et al (2019) revealed that negative allometric growth is influenced by the mudskipper swimming activity, thereby causing absorption of nutrients to reduce body weight. According to Ridho et al (2019) and Akinrotimi et al (2019) mudskipper do not grow in the same proportion, where the increase in length is faster than that in weight.…”
Section: Length-weight Relationship Of Mudskippermentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of the male fish is distributed at intervals of 8 to 19.99, while the frequency of the female fish is at intervals of 14 to 22.99. Similarly, based on long-class, the male and female fish ranges from 14-16.99 to 20-22.99 (Hui et al 2019;Sunarni et al 2019), which reduced the catch frequency because the fish caught are dominated by small fish that stand are evolving and have not yet reached the adult size. The frequency of male mudskipper (B. dussumieri) has decreased from long class as above from 10 to 11.99 to 14-15.99.…”
Section: Length Distribution Of Mudskipper (Male and Female)mentioning
confidence: 99%
“…Furthermore, research that has been conducted on the mudskipper has focused on the morphology, identification, and habitat type of the species (Rumahlatu et al 2020, Nugroho et al 2016 and biodiversity and abundance (Mahadevan and Ravi 2015, Maturbongs et al 2018. Specifically, a study on the length-weight relationship of the mudskipper showed that P. argentilineatus and P. gracilis collected from the mangrove of Kairatu Beach, Maluku, Indonesia had a negative allometric length-weight relationship (b < 3) (Taniwel et al 2020), the allometric length-weight relationship of Boleophthalmus pectinirostris (L.) was negative for males (b < 3) and positive for females (b > 3) (Sunarni et al 2019), while Periophthalmus chrysospilos Bleeker exhibited positive allometric growth patterns in Bayan Bay, Penang-Malaysia (Abdullah and Zain 2019), and three species of mudskipper -P. chrysospilos, P. gracilis, and Boleophthalmus boddarti (Pallas) -observed in the mangrove ecosystem of Sembilan, North Sumatera exhibited negative allometric growth patterns (Bidawi et al 2017).…”
Section: Introductionmentioning
confidence: 99%